OPTIMALISASI PEMANFAATAN TEKNOLOGI INFORMASI OLEH DANUNIT IDIK TERHADAP KUALITAS KERJA PROSES PENYIDIKAN DI DENPOM IV/2 YOGYAKARTA - Suhartini, Suhartini; Junaedi, Erwin; Irghi, Muhammad; Mega, Aryanti (PPM Sdirjianbang Akademi Militer, 2023)
The rapid technological development may cause disciplinary violations committed by military personnel become more complex, both in numbers and causes of the infringement. This condition requires Investigation Unit Commander Denpom IV/2 Yogyakarta to make advanced innovation and ability to use information technology running errands the investigation to become faster, proper, and efficient. Qualitative research methodology which is used in the research means a method that was done by searching the data through interviews, observations and documentations as a basis for making descriptive conclusions research or depicting it through the words. Based on the research that has been done, researchers came to some conclusions. They are: first, Investigation Unit Commander has not optimally utilized information technology in carrying out the task on the investigation process such as WhatsApp, Email, Digital forensics, Axiom, etc. This led to decreasing families and soldiers’ morale due to the lengthening of the temporary detention with uncertainty of decision. Second, optimalization the use of information technology by Investigation Unit Commander on the investigation process has had an effect in the improvement of the work quality on the investigation process which can be characterized by the promptness of investigation completion and its filing. Third, the commitment and support from the Military Police Detachment Commander are the driving factor in running their vision. Hence, improving the professionalism of the military police members among others with the education and training is the other supporting factor. The skillful character of the Investigation Unit Commander and its members shows that they work hard. There are some resistor factors in the optimalization. They are limited computer capacity in the investigation unit and also insufficient skills of investigation unit members in applying applications on smartphones that are useful in the investigation process.